Wednesday

April 1, 2015

April 1, 2015

Posted by **Kelli** on Wednesday, March 10, 2010 at 1:04pm.

- Algebra -
**Reiny**, Wednesday, March 10, 2010 at 1:12pmlog3 (2x – 1) – log3 (x – 4) = 2 , clearly x > 4

(2x-1)/(x-4) = 3^2

2x^2 -9x-5 = 0

(2x+1)(x-5) = 0

x = -1/2 or x = 5

but x > 4, so

x = 5

**Answer this Question**

**Related Questions**

ALGEBRA 1 - Lesson 3 Assignment .Explain the differences between solving these ...

Algebra 1 - Lesson 3 Assignment .Explain the differences between solving these ...

Precalculus - Please help me with these questions ASAP!! Suppose that f(x)=log3...

Math - Solve the logarithmic equation. Express your solutions in exact form only...

Math - (I have two questions) 1. Solve for x without a calculator: log3(x^2)=...

Math - Express the following as a logarithm and simplify. 1. log(3x^2 + 11x - 20...

Math - Express the following as a logarithm and simplify. 1. log(3x^2 + 11x - 20...

Math - logs - log_3(2x - 1) = 2, Find x. Here's what I've done: log_3(2x) * ...

Algebra ll - I need help, can someone guide me through this problem? log3(x + 2...

Algebra 1 - Explain the differences between solving these two equations: Brake ...